Predicting chaotic climates: from Earth to super-Earths? - Read, P (2010)
The prediction of atmospheric behaviour for the Earth has been a major arena for the application of complex mathematical ideas and techniques to geophysics and astronomy. Objective forecasting of the weather provided the first stimulus for the development of numerical methods to integrate the equations of fluid motion by L. F. Richardson in the early 20th century, leading on to their implementation in electronic computers in the 1940s and 1950s. Such an approach has now reached a highly sophisticated state with weather and climate models attempting to forecast weather and climate changes in immense detail. Such techniques have been applied to model the atmospheres of other planets in the Solar System since the 1960s, and are catching up rapidly in their sophistication with models used for the Earth. But with the expanding discoveries of planets around other stars, it is likely that alternative approaches may be needed that are more general but seek to quantify trends in the gross features of atmospheric circulation systems as a function of a small number of global parameters. By the study of simple analogues, either in the form of simplified numerical models or laboratory experiments, considerable insights may be gained as to the likely roles of planetary size, rotation, thermal stratification and other factors in determining the principal length scales, styles of global circulation and dominant waves and instability processes active in all planetary atmospheres. In this review, we explore aspects of these analogues and demonstrate the importance of a number of key dimensionless parameters, most notably thermal Rossby and Burger numbers and a measure of the dominant frictional or radiative timescale, in defining the type of circulation regime to be expected in a prototype planetary atmosphere subject to axisymmetric driving. These considerations help to place Mars, Venus, Titan and Earth into an appropriate context, and may also lay the foundations for predicting and understanding the climate and circulation regimes of (as yet undiscovered) Earth-like extrasolar planets. However, as recent discoveries of 'super-Earth' planets around some nearby stars are beginning to reveal, the parameter space determined from axisymmetrically-forced prototype atmospheres may be incomplete and other factors, such as the possibility of tidally-locked rotation and tidal forcing, may also need to be taken into account for some classes of extra-solar planet. © 2010 American Institute of Physics.